Teachers' digital competency in using digital lesson content for teaching and learning in secondary schools in Zanzibar (Educational Dimension, 2024)
Teachers' digital competence has been emphasised for improving quality education at all levels worldwide. In Zanzibar, the educational policy adopted digital lesson content (DLC) for teaching and learning in ordinary secondary schools. The study investigated the teachers' digital competence and factors that affect their use of DLCs for teaching and learning. One fifty-four (154) secondary school teachers from Wete district were given 5-point Likert Scale questionnaires. Inferential and descriptive statistics were used to analyse the collected data with the help of SPSS version 25. The study found that the teachers' digital competence is high for using it in teaching and learning. Also, it was observed that the digital competence of the teachers was significantly associated with their attitude and in-service training. The paper concludes that using DLCs in third-world countries takes work. However, it is possible if the government and private sectors, such as NGOs, invest seriously in secondary school levels. Also, it recommends that responsible leaders distribute digital devices and plan regular in-service training for teachers on integrating DLCs at secondary schools to cope with the global vision of 2025. Last, the paper recommends further study considering a large sample size of secondary schools in Zanzibar through random sampling techniques.